THE MAIDEN AND WATER – On the Dynamics of the Relation between Women and Nature (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
The paper discusses ways of modelling the relation between the maiden and water in different motifs of oral lyric songs, how women who sing those songs see themselves in the world and how women in traditional culture are positioned in relation to the nature/culture opposition. The ambiguity of the aforementioned relation is demonstrated. The songs model water as a feminine space, but as a space where the maiden is endangered as well. In this sense, they confirm the position of a woman as a being between nature and culture. The maidens in oral lyric songs reign over the fruitful, creative and healing powers of water, they are the masters of the torrent and they move through aquatic landscape freely, but they are also endangered in contact with water and they drown in it. The same ambiguity is perceived when we observe the relation of lyric songs with motifs of the maiden and water to the patriarchal order – the said songs can confirm that order, or contest it.
Keywords: oral lyric songs; woman; water, nature/culture; space